MARKET-BASED MANAGEMENT (MBM) APPROACH TO SUCCESS IN HIGHER EDUCATION: LESSONS FROM A MID-SIZED BUSINESS INSTITUTE: Received: 26th June 2023; Revised: 13th October 2023, 18th October 2023, 19th October 2023; Accepted: 26th October 2023 - Zaidi, Uzma (PUPIL: International Journal of Teaching, Education and Learning, 2023)
This research examines a mid-sized business institute, SZABIST-Dubai by using a qualitative research methodology of case study. The research objective is to explore the adoption of Market-Based Management (MBM) for its application in Higher Education and to recommend Market Based Management that is lean and agile enough to identify local market opportunities, understand its unique requirements and initiate processes to capture these opportunities before they are lost to competition. Some significant findings of this paper are the survival and profitability challenges faced by SZABIST and a unidirectional centralised decision-making model that is adapted currently at the institute. The outcome of this paper is its proposition of Market Based Management (MBM) as a tool to evolve into a knowledge-based learning organization that is more responsive to regional and local challenges. The most significant contribution of this paper towards this objective is the founding of Task Teams that transform tacit learning into explicit knowledge through the process of socialisation. This paper may be useful for future researchers who wish to extend these findings to other higher educational institutes.